Military Injury Biomechanics : The Cause and Prevention of Impact Injuries - Franklyn, Melanie; Lee, Peter Vee Sin (Boca Raton, FL : CRC Press, 2017)
Military Injury Biomechanics: The Cause and Prevention of Impact Injuries is a reference manual where information and data from a large number of sources, focussing on injuries related to military events, has been critically reviewed and discussed. The book covers the cause and prevention of impact injuries to all the major body regions, while topics such as the historical background of military impact biomechanics, the history and use of anthropomorphic test devices for military applications and the medical management of injuries are also discussed. An international team of experts have been brought together to examine and review the topics. The book is intended for researchers, postgraduate students and others working or studying defence and impact injuries.--Provided by publisher.
chapter 1 Introduction -- chapter 2 Ballistic Threats and Body Armour Design -- chapter 3 Blast Physics and Vehicle Response -- chapter 4 Injury Scoring Systems and Injury Classification -- chapter 5 The Medical Management of Military Injuries -- chapter 6 Anthropomorphic Test Devices for Military Scenarios -- chapter 7 The Mechanical Behaviour of Biological Tissues at High Strain Rates -- chapter 8 The Skull and Brain: Test Methods, Behind Armour Blunt Trauma and Helmet Design -- chapter 9 The Skull and Brain: Mechanical Properties of the Brain under Impact -- chapter 10 The Skull and Brain: Computer Models for the Head and Its Protection -- chapter 11 The Neck: Neck Injuries in Military Scenarios -- chapter 12 The Thoracolumbar Spine and Pelvis: Injury Criteria for Traumatic Spinal and Pelvic Injury and Their Current Applications -- chapter 13 The Thoracolumbar Spine: Cadaveric Testing under Vertical Loading -- chapter 14 The Thorax and Abdomen: Behind Armour Blunt Trauma -- chapter 15 The Lower Extremities: Cadaveric Testing, Anthropomorphic Test Device Legs and Injury Criteria -- chapter 16 The Lower Extremities: Computational Modelling Attempts to Predict Injury.
Keywords: Medicine, Military; War wounds; Blunt trauma; Biomedical Engineering; Biotechnology; MEDICAL / Biotechnology